The Role of Commercial Banks in Financing Small and Medium Businesses in Uzbekistan (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2026)
Small and medium enterprises (SMEs) are recognized worldwide as cornerstones of economic development, fostering innovation, employment, and sustainable growth. In Uzbekistan, the SME sector’s expansion has been constrained by various obstacles, most notably limited access to formal finance. Commercial banks, as primary financial intermediaries, have played a critical yet evolving role in addressing this gap. This article provides an in-depth analysis of the role of commercial banks in financing SMEs in Uzbekistan, examining historical context, sectoral reforms, lending trends, government and international support frameworks, and the challenges and opportunities inherent in current practice. Using comparative insights and relevant case studies, the article culminates with specific recommendations for policy-makers, banks, and the broader financial ecosystem to unlock the full potential of SMEs in Uzbekistan.